(untitled) (Research, Society and Development, 2021)
This study longitudinal investigated food consumption and factors related to weight variation in 81 adult patients with Non-Alcoholic Fatty Liver Disease (NAFLD) during the COVID-19 pandemic. Sociodemographic, anthropometric, physical activity and food intake data were collected during two periods: before and during the pandemic. For analysis, variations in weight were divided into two categories: weight gain less than or equal to two kilos and weight gain greater than two kilos. Mann Whitey test was used to verify the difference between the medians, while Spearman’s correlation coefficient to calculate correlations, Fisher’s exact test to assess associations. The significance level adopted in the decision of the tests was 5%. Results showed increases in the consumption of processed and ultra-processed foods among NAFLD patients alongside a reduction in the consumption of natural or minimally processed foods. Both findings were more frequent among patients demonstrating weight gain greater than two kilograms. However, analysis of the nutritional composition of patients’ diets revealed increases in carbohydrate consumption to be the only factor significantly correlated with weight gain. There was a high percentage of individuals who did not practice physical exercise before the pandemic, and this number was exacerbated during home isolation. Thus, it is observed that NAFLD patients have difficulty maintaining a healthy lifestyle and these difficulties have worsened during the pandemic, as reflected by weight gain. Therefore, it is suggested that specialized nutritional assistance be aimed at NAFLD patients seeing as they are at an increased risk for progression to more severe forms of COVID-19.